Cross‐Coupled Ratio Control Structure - Yesil, Engin; Guzelkaya, Mujde; Eksin, Ibrahim; Tekin, O. Aydin (Informa UK Limited, 2007)
Abstract In this paper, a cross‐coupled ratio control structure with two blend stations has been proposed. The main feature of the proposed structure is to give a good ratio performance for both set‐point changes and load disturbances that might occur in any one of the two loops. A simple tuning procedure for the inner controllers of the two loops and an easy design methodology for the blend stations have been proposed in order to avoid any significant tuning and design effort for the implementer. The proposed structure is realized on a microcontroller based system. This cross‐coupled ratio control structure that has been embedded into the microcontroller is then used to maintain the prescribed ratio “a” of the two processes, namely heat transfer process trainer (PT 326‐Feedback) and process control simulator (PCS 327‐Feedback). The same two processes are run under another alternative ratio control structure and the results are compared with each other.